Ketoprofen and mefenamic acid potency following odontectomy - Aguas, Kareen Anne; Balanag, Jonathan Y.
This study aimed to test the potency of oral ketoprofen as a post-operative drug for patients who had odontectomy as compared to mefenamic acid which is at present the most commonly used non-steroidal anti-inflammatory drug used in the clinics. Forty one patients in the Out Patient Department of the Philippine General Hospital and in the Oral Surgery Department of the UP College of Dentistry who underwent removal of their lower third molars were used in the study. They were given one of the drugs to take after surgical treatment for three days. Pre-operative and post-operative photographs were taken and pain analogue and pain relief sheets were answered by the patients to gauge the quality of pain and relief felt following drug intake. Data were statistically analyzed with the Chi-square test with a 0.05 level of significance 80% of patients who took ketoprofen experienced complete relief as compared to mefenamic acid with only 38%. For swelling, a micrographic designer software was used. Results showed a mean change of 1mm in patients who took ketoprofen. This study concludes that Ketoprofen provides superior analgesia compared to Mefenamic Acid.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Non-Steroidal Anti-Inflammatory Drugs (NSAID).; Ketoprofen; Mefenamic acid